Ultra-high-frequency radio-frequency acoustic molecular imaging with saline nanodroplets in living subjects - Chen, Yun-Sheng; Zhao, Yang; Beinat, Corinne; Zlitni, Aimen; Hsu, En-Chi; Chen, Dong-Hua; Achterberg, Friso; Wang, Hanwei; Stoyanova, Tanya; Dionne, Jennifer; Gambhir, Sanjiv Sam (Nature nanotechnology, 2021)
Molecular imaging is a crucial technique in clinical diagnostics but it relies on radioactive tracers or strong magnetic fields that are unsuitable for many patients, particularly infants and pregnant women. Ultra-high-frequency radio-frequency acoustic (UHF-RF-acoustic) imaging using non-ionizing RF pulses allows deep-tissue imaging with sub-millimetre spatial resolution. However, lack of biocompatible and targetable contrast agents has prevented the successful in vivo application of UHF-RF-acoustic imaging. Here we report our development of targetable nanodroplets for UHF-RF-acoustic molecular imaging of cancers. We synthesize all-liquid nanodroplets containing hypertonic saline that are stable for at least 2 weeks and can produce high-intensity UHF-RF-acoustic signals. Compared with concentration-matched iron oxide nanoparticles, our nanodroplets produce at least 1,600 times higher UHF-RF-acoustic signals at the same imaging depth. We demonstrate in vivo imaging using the targeted nanodroplets in a prostate cancer xenograft mouse model expressing gastrin release protein receptor (GRPR), and show that targeting specificity is increased by more than 2-fold compared with untargeted nanodroplets or prostate cancer cells not expressing this receptor.